ANALISIS PROGRAM LAFADZ DAN NAGHAM SEBAGAI MEDIA DAKWAH DI TVRI SUMATERA BARAT - Rahmat Hafizullah; Ali Nupiah (KINEMA: Jurnal Komunikasi dan Penyiaran, 2023)
Abstract : Television media broadcast various da'wah programs, such as religious dialogues, grand recitation programs, films with da'wah messages, and competitions to become preachers. However, keep in mind that the data presented does not cover all da'wah shows on television, given the many national and private television channels in Indonesia. Among the many television da'wah programs, the Lafadz and Nagham programs on TVRI West Sumatra became interesting when researchers found the phenomenon that the material delivered by the preacher contained da'wah messages and there were elements of da'wah in the program. This research will discuss more deeply about the lafadz and nagham programs which are used as propaganda media as well as the elements of da'wah contained in the lafadz and nagham programs on TVRI West Sumatra.This research is a qualitative research. Data collection was carried out using the interview method with program producers Lafadz and Nagham. This study aims to analyze the Lafadz and Nagham Programs as Da'wah Media at TVRI West Sumatra. The research process will describe the lafadz and nagham programs based on the theories put forward by experts and then enter the data obtained through interviews, observation and documentation.Based on the results of the research, it can be concluded from this study that the Lafadz and Nagham programs contain da'wah messages about learning recitation and tahsin of the Qur'an and each segment contains an invitation to the audience to always read and study the Qur'an. The lafadz and nagham programs have 6 elements of da'wah, namely: Da'i, Mad'u, Maddah, Wasilah, Tariqah, Atsar.Keywords : Media, Dakwah, Program, Nafadz and Nagham.